Peningkatan Pemahaman Konsep Bangun Datar dengan Menggunakan Media Realia pada Pembelajaran Matematika pada Siswa Sekolah Dasar - Arifin, Muhammad Nur; Chumdari, Chumdari; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2019)
The purpose of this research is to improve the concept understanding of twodimentionalfigure by using Media Realiaof the student in Grade IIIB of state Primary Schoolof Bratan 1 in Academic Year 2016/2017.This research used the classroom action researchwith two cycles. Each cycle consisted of four phases, namely:planning, implementation,observation, and reflection. The subjects of the research were the students as many 34 studentsin Grade IIIB of the school. Data analysis techniques that use data collection, data reduction,data presentation, and withdrawal of conclusions. Data validity using technique triangulationand source triangulation.The results showed that by using Media Realia can improve theunderstanding of two-dimentional figure on IIIB students SD Negeri Bratan 1 academic year2016/2017. Before using Media Realia is seen, the students who reach the KKM consist ofonly 11 students or 32,35% in pre-action data. In the first cycle by using Media Realia studentsmastery increased to 67,65%. In the second cycle by using Media Realia students mastery roseto 85,3%. From the results of my research can be concluded that by using Media Realiacanimprove understanding of two-dimentional figure state in the students of grade IIIB SD NegeriBratan 1 academic year 2016/2017.